IMPLEMENTASI KEBIJAKAN RETRIBUSI PARKIR TERHADAP PAD - Semdi J E. Sopbaba; Sugeng Rusmiwari; Willy Tri Hardianto (Universitas Tribhuwana Tunggadewi, 2015)
Abstract: Provision of autonomy to regions aims to give authority to the regions to organize and manage his own household, in order to improve the efficiency and effectiveness of governance in the context of public service and implementation. One source of revenues which is fairly great is parking retribution. This sector is one of important sources of revenue as it always has been developed along with the development of the region (the city), so that when it is managed properly, it can support local revenue (PAD). The research method is qualitative, describing and revealing problems and condition in the way they are. The informants were taken by using purposive sampling and snowball sampling technique, for collecting data through interviews, observation, and documentation. The data were analyzed in three stages, namely data reduction, data presentation, and conclusion. The results showed that in the last three years (2009 up to 2011) parking retribution give retribution in average of 1.49% to local revenue in Batu Cities in every year. This shows that the contribution of parking retribution supports the local revenue in Batu but is still relatively small. Furthermore, the collecting of parking retribution in Batu is carried out through several phases including: a) determination of parking object, b) collection of parking retribution, and c) billing. The factors affecting the collection of parking retribution in Batu City are: 1) lack of public awareness, and 2) lack of control system. Keywords: Implementation, Parking Retribution, and Local Revenue (PAD) Abstrak: Pemberian otonomi kepada daerah bertujuan memberi kewenangan kepada daerah untuk mengatur dan mengurus rumah tangganya sendiri, guna meningkatkan efisiensi dan efektifitas penyelenggaraan pemerintahan dalam rangka pelayanan kepada masyarakat dan pelaksanaan pembangunan. Salah satu sumber penerimaan retribusi daerah yang cukup besar adalah retribusi parkir. Sektor ini merupakan salah satu sumber penerimaan yang penting karena selalu mengalami perkembangan seiring dengan berkembangnya suatu kawasan (kota), sehingga bila dikelolah dengan baik dapat menunjang pendapatan asli daerah (PAD). Metode penelitian yang digunakan bersifat kualitatif, denga cara mendeskripsikan dan mengungkapkan masalah dan keadaan apa adanya. Pengambilan informan mempergunakan teknik purposive sampling dan snowball sampling sedangkan teknik pengumpulan data melalui interview, observasi dan dokumentasi. Data dianalisis melalui tiga tahapan, yakni reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukan bahwa pada tiga tahun terakhir (2009 S/D 2011) retribusi parkir memberikan kontribusi sebesar rata-rata 1,49% terhadap Pendapatan Asli Daerah di Kota Batu tiap tahunnya. Hal ini menunjukan bahwa kontribusi retribusi parkir dalam menunjang PAD di Kota Batu masih tergolong kecil. Selanjutnya pemungutan retribusi parkir di Kota Batu dilaksanakan melalui beberapa tahapan antara lain : a) Penetapan Objek Parkir; b) Pemungutan Retribusi Parkir dan c) Penagihan. Adapun faktor-faktor yang mempengaruhi pemungutan retribusi parkir di Kota Batu antara lain: 1) Rendahnya Kesadaran masyarakat; dan 2) Rendahnya Sistem Pengawasan. Kata Kunci: Implementasi, Retribusi Parkir, Pendapatan Asli Daerah (PAD)